Risk of malignancy in rheumatoid arthritis patients initiating biologics: an historical propensity score matched cohort study within the French nationwide healthcare database. Issue 2 (23rd June 2022) - Seror, Raphaele; Lafourcade, Alexandre; De Rycke, Yann; Pinto, Sandrine; Castaneda, Johann; Fautrel, Bruno; Mariette, Xavier; Tubach, Florence
Abstract : Objective: To compare the risk of malignancy between patients with rheumatoid arthritis (RA) initiating their first biological disease-modifying antirheumatic drug (bDMARD) and those continuing conventional synthetic DMARDs (csDMARDs). Methods: Nine-year historical Propensity Score (PS) matched cohort study within the French national healthcare database (87% of the French population; ~57 million people), including adults RA without malignancy. Exposures started with the first use of any systemic treatment (csDMARDs and/or bDMARDs). Incident users of bDMARDs were matched on a dynamic PS to patients continuing csDMARDs. Their risk of malignancy was compared by Cox model. Results: From 1 January 2007 to 31 December 2014, 83 706 patients with RA started their first systemic treatment (63 837 remained on csDMARDs and 19 869 initiated a bDMARD during follow-up). After dynamic PS matching, 19 727 bDMARD initiators were compared with 19 727 RA remaining on csDMARDs. They did not statistically differ in risk of overall malignancies (HR 0.99 (95% CI 0.86 to 1.14)), solid cancer (HR 0.95 (95% CI 0.82 to 1.11)), nor lymphoma (HR 1.35 (95% CI 0.72 to 2.53)). Results were similar when bDMARDs were given as monotherapy or in association with csDMARDs. Analyses restricted to patients starting TNF inhibitor as first bDMARD compared with matched RA remaining on csDMARDs, provided similar results (HR for overall malignancy 1.03 (95% CI 0.88 to 1.21)). Sensitivity analyses, varying carry-over periods (up to 5 years) to define risk periods, provided similar results. Conclusions: In this historical cohort study within the French nationwide healthcare database, the risk of overall, solid or haematological malignancies did not significantly differ between patients with RA initiating bDMARD and those continuing csDMARDs.